Unraveling the Molecular Pathogenesis of Protein C Deficiency–Associated VTE: Insights from Protein C Mutations C238G and R189W in Thai Patients - Tanratana, Pansakorn; Seanoon, Karnsasin; Payongsri, Panwajee; Kadegasem, Praguywan; Chuansumrit, Ampaiwan; Sirachainan, Nongnuch (Thrombosis and Haemostasis, 2024)
Protein C (PC) deficiency is a well-established risk factor for thromboembolism (TE), commonly manifesting in pediatric patients. This study aimed to elucidate the pathogenic mechanisms of two novel PC mutations, C238G and R189W, identified in Thai children with both venous and arterial TE.The effects of wild-type (WT), C238G, and R189W PC variants were investigated through transient transfection of HEK293T cells. PC secretion levels were measured, and immunofluorescence analysis was performed to assess intracellular localization. ER stress-related gene expression and UPR activation were evaluated. Structural analysis was conducted to explore the significance of the C238 and R189W residue in PC functionality.The C238G mutation led to a severe 95% reduction in PC secretion, while R189W showed a 30% decrease compared with WT. Immunofluorescence revealed that C238G-PC was predominantly retained in the ER, indicating protein misfolding. C238G-expressing cells exhibited significant upregulation of ER stress-related genes and UPR activation. In contrast, R189W resulted in only a modest increase in UPR gene expression, suggesting a less pronounced impact on protein folding and secretion. Structural analysis demonstrated the critical role of the C238 residue in maintaining PC's disulfide bond and overall conformation.This study reveals distinct molecular mechanisms by which the C238G and R189W mutations contribute to PC deficiency and increased thrombotic risk. The findings emphasize the essential role of the C238 residue in preserving PC structure and secretion, enhancing the understanding of PC deficiency-associated TE in pediatric patients.
Keywords: PC mutations; PC deficiency; venous thromboembolism; protein misfolding; ER stress